Androgen Receptor, EGFR, and BRCA1 as Biomarkers in Triple-Negative Breast Cancer: A Meta-Analysis. (28th January 2015) - Zhang, Li; Fang, Cheng; Xu, Xianqun; Li, Anling; Cai, Qing; Long, Xinghua
Abstract : Objective . More and more evidences demonstrate that androgen receptor (AR), epidermal growth factor receptor (EGFR), and breast cancer susceptibility gene 1 (BRCA1) have unique clinical implications for targeted therapy or prognosis in triple-negative breast cancer (TNBC). Therefore, we conducted a meta-analysis to summarize the possible associations. Methods . We retrieved published articles about AR, EGFR, and BRCA1 in TNBC from PubMed and EMBASE. The analysis was performed with Rev-Man 5.2 software. Results . A total of 38 articles were eligible for the meta-analysis. Our study showed that the expression level of EGFR (OR = 6.88, P < 0.00001 ) and the prevalence of BRCA1 mutation (RR = 5.26, P < 0.00001 ) were higher in TNBC than non-TNBC. In contrast, the expression level of AR was lower in TNBC than non-TNBC (OR = 0.07, P < 0.00001 ). In the subgroup related to EGFR expression, the level of EGFR expression was significantly increased in Asians (OR = 9.60 ) compared with Caucasians (OR = 5.53 ) for TNBC patients. Additionally, the prevalence of BRCA1 mutation in Asians (RR = 5.43, P < 0.00001 ) was higher than that in Caucasians (RR = 5.16, P < 0.00001 ). Conclusions . The distinct expression of AR and EGFR and the prevalence of BRCA1 mutation indicated that AR, EGFR, and BRCA1 might be unique biomarkers for targeted therapy and prognosis in TNBC.